2022
DOI: 10.1155/2022/5292454
|View full text |Cite|
|
Sign up to set email alerts
|

Tracking of Gymnast’s Limb Movement Trajectory Based on MEMS Inertial Sensor

Abstract: In order to track the limb movement trajectory of gymnasts, a method based on MEMS inertial sensor is proposed. The system mainly collects the acceleration and angular velocity data of 11 positions during gymnastics by constructing sensor network. Based on the two kinds of preprocessed data, the parameters such as sample mean, standard deviation, information entropy, and mean square error are calculated as classification features, the support vector machine (SVM) classification model is established, and the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Li et al [23] proposed an SVM-based model for the recognition of gymnastic movements. Rustam [24] presented a deep stacked multilayered perceptron model for HAR.…”
Section: Related Workmentioning
confidence: 99%
“…Li et al [23] proposed an SVM-based model for the recognition of gymnastic movements. Rustam [24] presented a deep stacked multilayered perceptron model for HAR.…”
Section: Related Workmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%